Doxycycline to treat levodopa-induced dyskinesias in Parkinson's disease: a preliminary study - Bruno Lopes Santos-Lobato; Manuelina Mariana Capellari Macruz Brito; Ângela Vieira Pimentel; Rômulo Torres Oliveira Cavalcanti; Elaine Del-Bel; Vitor Tumas (Arquivos de Neuro-Psiquiatria)
Background Levodopa-induced dyskinesia (LID) is a common motor complication of levodopa therapy in patients with Parkinson's disease (PD). Doxycycline is a widely used and inexpensive tetracycline with anti-inflammatory properties. Objective To evaluate the efficacy and safety of doxycycline in patients with PD and LID. Methods This was an open-label, uncontrolled, single-arm, single-center, phase 2 proof-of-concept study in patients with PD with functional impact of dyskinesia, which used levodopa three times daily, in a movement disorders clinic in Brazil. Participants were treated with doxycycline 200 mg/day for 12 weeks, with evaluations at baseline, week 4, and week 12 of treatment. The primary outcome measure was the change from baseline in the Unified Dyskinesia Rating Scale (UDysRS) total score at week 12, evaluated by two blinded raters. Key secondary outcomes measures were OFF time and ON time with troublesome dyskinesia in the PD home diary. Results Eight patients with PD were treated and evaluated. Doxycycline 200 mg/day reduced the UDysRS total score at week 12, compared with baseline (Friedman χ2 = 9.6; p = 0.008). Further, doxycycline reduced the ON time with troublesome dyskinesia (Friedman χ2 = 10.8; p = 0.004) without worsening parkinsonism. There were no severe adverse events, and dyspepsia was the commonest event. Conclusion In this preliminary, open-label and uncontrolled trial, doxycycline was effective in reducing LID and safe after a 12-week treatment. Further well-designed placebo-controlled clinical trials with a longer duration and a larger number of participants are needed. Clinical trial registration https://ensaiosclinicos.gov.br, identifier: RBR-1047fwbf